Trends in the Treatment of Adults with Ureteropelvic Junction Obstruction - Jacobs, Bruce L. (Mary Ann Liebert, Inc., 2013)
BACKGROUND AND PURPOSE: Minimally invasive pyeloplasty is an effective treatment for patients with ureteropelvic junction obstruction that offers quicker convalescence than open pyeloplasty. Technical challenges, however, may have limited its dissemination. We examined population trends and determinants of surgical options for ureteropelvic junction obstruction. PATIENTS AND METHODS: Using the State Inpatient and Ambulatory Surgery Databases for Florida, we identified adults who underwent ureteropelvic junction obstruction repair between 2001 and 2009. After determining the surgical approach (minimally invasive pyeloplasty, open pyeloplasty, or endopyelotomy), we estimated annual utilization rates and the effects of patient, surgeon, and hospital predictors on surgery type, using multilevel multinomial logistic regression. RESULTS: Rates of minimally invasive pyeloplasty increased 360% (P for monotonic trend < 0.01), while rates of open pyeloplasty decreased 56% (P<0.01). Rates of endopyelotomy were substantially higher and remained relatively stable (P=0.27). Compared with open pyeloplasty, minimally invasive pyeloplasty was used more commonly among patients with private insurance (odds ratio [OR] 1.6; 95% confidence interval [CI], 1.2–2.3), those treated at teaching hospitals (OR 1.6; CI 1.0–2.6), and those treated by high-volume surgeons (OR 2.9; CI 2.0–4.2). Its use was less frequent among patients with multiple comorbidities (OR 0.53; CI 0.37–0.76). Similar associations were observed when comparing receipt of minimally invasive pyeloplasty with endopyelotomy; however, patients who underwent endopyelotomy were older. CONCLUSIONS: The use of minimally invasive pyeloplasty has dramatically increased, largely replacing open pyeloplasty, while the use of endopyelotomy, albeit significantly more common than the other approaches, has remained stable. The surgical approach is influenced by several patient, surgeon, and hospital factors.